2005
DOI: 10.1002/bse.446
|View full text |Cite
|
Sign up to set email alerts
|

Are business students buying it? A theoretical framework for measuring attitudes toward the legitimacy of environmental sustainability

Abstract: Environmental sustainability has begun to penetrate the business school curriculum. Whether it ultimately becomes a key component of managerial decision-making models will depend upon whether it is perceived as legitimate within the context of profit-making enterprises. This paper draws upon the cognitive psychology and organizational legitimacy literatures to develop a conceptual framework for operationalizing perceived legitimacy. This framework can be used to develop survey instruments and simulations that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 30 publications
1
52
1
4
Order By: Relevance
“…Measures of student attitudes toward sustainable business practices were developed by the authors informed by the writing of Thomas (2005). Six items were included, four items addressing the value of environmental sustainable business practices (e.g., ''I believe environmental sustainability business practices are the 'right thing' to do, regardless of their pragmatic utility (benefits) to the organization'') and two of items addressed including environmental sustainability concepts and strategies in core business courses (e.g., ''Introducing environmental sustainability concepts and strategies into courses will increase student concerns for the environment'').…”
Section: Attitudes Toward Sustainable Business Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Measures of student attitudes toward sustainable business practices were developed by the authors informed by the writing of Thomas (2005). Six items were included, four items addressing the value of environmental sustainable business practices (e.g., ''I believe environmental sustainability business practices are the 'right thing' to do, regardless of their pragmatic utility (benefits) to the organization'') and two of items addressed including environmental sustainability concepts and strategies in core business courses (e.g., ''Introducing environmental sustainability concepts and strategies into courses will increase student concerns for the environment'').…”
Section: Attitudes Toward Sustainable Business Practicesmentioning
confidence: 99%
“…There already appears to be a commonly held belief that business students are only interested in the bottom-line and are selfserving business types (Lopez et al, 2005). Given that the business students today are the business leaders of tomorrow, and coupled with the negative stereotypes surrounding them, the lack of support for sustainable business practices is a cause for concern (Springett and Kearins, 2001;Thomas, 2005).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent evidence by Hopkins (2012) suggests that during the past 20 years, education for sustainable development has grown, evolved and matured within higher education. Also Geli de Ciurana and Filho (2006) reported that HEIs view sustainability as a central goal, especially business schools who have incorporated SD into their teaching structure (Cortese, 2003;Jones, Selby, Sterling & IIED, 2010;Lozano, 2006;Thomas, 2005;Velazquez, Munguia & Sanchez, 2005;Wemmenhove & de Groot, 2001). …”
Section: Education For Sustainable Development In Higher Education Inmentioning
confidence: 99%
“…Although an increasing number of individuals and groups are engaged in some form of ESD, Cortese thinks that it is often the graduates of the most prestigious universities who become leaders that adopt an "unhealthy, inequitable, and unsustainable path" (p. 16). For instance, the Aspen Institute's 2003 report of MBA students' attitudes about business and society showed that almost a third of students in top MBA programs in the United States, Canada, and the UK believed that the environmental responsibility of a company did not extend beyond abiding by the law (Thomas, 2005). Four years later, when the Aspen Institute conducted its third online survey to which 1,943 MBA students enrolled at 15 business schools responded, these attitudes had not changed significantly.…”
Section: Esd and The Role Of Higher Educationmentioning
confidence: 99%